Peran Pengawasan Konsumen dalam Transaksi Bisnis Online - Sri Anafarhanah (Alhadharah: Jurnal Ilmu Dakwah, 2017)
Convenience offered by online business transactions or more commonly called e-commerce, the customer does not escape the risks that will be borne by both parties, the risk can be technical and non technical. Problematic in online transactions that often happens transactions are fraud in transactions and mismatch of goods with specifications. In addition, the risk of hidden defects of goods traded is also the largest mode of online business actor either intentionally or unintentionally. To avoid such losses, the consumer must be smart to recognize the type of transaction, the seller / merchant, and the product will be purchased. This action is done as a form of consumer supervision of online business transactions. In order for consumers not always harmed, the government has issued Law No. 8 of 1999 on consumer protection. In addition to the law, consumers are also protected by the Indonesian Consumers Foundation (YLKI). YLKI is a non-governmental and non-profit organization that aims to increase consumer's critical awareness of rights and responsibilities so as to protect itself and its environment. Meanwhile, from the supervision of consumers as transactors, can apply preliminary supervision, supervision conducted in conjunction with the implementation of activities and supervision of feedback.